Comparative analysis of women-led and agrarian reform beneficiaries cooperatives in Davao City: Cocoa value chain using a gender lens in the face of vulnerability - Lopez, Mitchiko Ariola; Lapitan, Aileen V.; Aranas, Mia Barbara D.; Faylon, Rassel P.; Anastacio, Nico Jayson C.; Predo, Canesio D.; Flores, Emmanuel (University of the Philippines, 2023)
This paper presents a comparative study using a gender lens in examining how two groups engaged in the cocoa value chain in Davao City, Philippines, addressed challenges and leveraged innovative strategies amidst a backdrop of vulnerability. The first group is a womenled cooperative, while the other group is a cooperative of Agrarian Reform Beneficiaries (ARB) operating for 35 and 30 years, respectively, within conflict and nonconflict areas. A rapid value-chain assessment was conducted through a series of focus group discussions and key informant interviews with members/officers of the cooperatives. The assessment was also supported by the available secondary data. Results highlight the unique roles and contributions of women in Davao City’s cocoa value chain. A women-led cooperative has a one-of-a-kind innovation of buying and consolidating cocoa pods from tagged trees rather than wet or dried beans to ascertain ‘tree-to-bar’ quality standards. It is a way of navigating various challenges in cocoa production—accessibility of needed services, lack of postharvest facilities, and marketing difficulties within a community in transition from conflict. The ARB cooperative with its access to diverse services, and capital (financial, equipment, facilities) has diversified from dried fermented cocoa beans to a wide array of value-added products involving mostly women workers. Innovation thrives when women workers and/or leaders have agency and power. Innovations are eased by persistent gender sensitivity and mainstreaming efforts. Recommendations leading to desired transformative change in agri-food systems in this part of the world are also discussed in the paper.